Bengali questionnaire validation among geriatric population visiting homeopathic hospital and subsequent open observational trial evaluating effectiveness of homeopathic treatment. Issue 2 (August 2017) - Das, Kaushik Deb; Patra, Sutanu; Koley, Munmun; Saha, Subhranil
Abstract: Aims: The authors intend to develop translated Bengali questionnaires measuring depression, stress, mindfulness and quality of life among geriatric population seeking homeopathic care and to examine effectiveness of homeopathic treatment subsequently in the said conditions by an open, observational trial. Methods: A mixed method bi-phasic study – a cross-sectional validation study in the first phase, followed by open, observational trial in the second phase was conducted using 4 translated questionnaires – Geriatric Depression Scale, Perceived Stress Questionnaire, Mindfulness Attention Awareness Scale, and Quality of Life Scale. Hamilton's Anxiety Scale was physician-administered; hence translation, further validation and testing cross-cultural adaptability was unnecessary. Results: Total 110 geriatric patients were enrolled; 60 suffered from depression, 86 from stress, 59 from anxiety. Exploratory principal component analysis using varimax rotation provided indications for construct validity. Questionnaires were internally consistent (Cronbach's α 0.745–0.926); with acceptable concurrent validity (Pearson's r 0.552–0.884). After the questionnaires were found valid by psychometric evaluation, the subsequent open observational trial for 3 months demonstrated individualized homeopathic treatment to be effective for the said conditions by changing the questionnaire scores significantly (P < 0.001; Cohen's d 0.568–1.499). Conclusion: The questionnaires appeared valid and reliable. Effect sizes were promising, forming basis of up-taking efficacy trials. Limited generalizability of treatment effects necessitates cautious interpretation. Trial registration: CTRI/2015/06/005927.